2021
DOI: 10.1210/clinem/dgab137
|View full text |Cite
|
Sign up to set email alerts
|

Fenofibrate Delays the Need for Dialysis and Reduces Cardiovascular Risk Among Patients With Advanced CKD

Abstract: Context Fenofibrate provides limited cardiovascular (CV) benefits in the general population; however, little is known about its benefit among advanced chronic kidney disease (CKD) patients. Objective This study compared outcomes among advanced CKD patients treated with fenofibrate, statins, a combination of both, and none of these. Design National cohort stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…Patients without previous diagnosis of any kind of hyperlipidemia, with incomplete demographics, who were younger than 20 years, or who had undergone renal transplantation prior to the index date were excluded. The remaining patients were divided into four groups (fibrate, statin, combination, and non-user groups) according to their use of lipid-lowering medications within 3 months prior to the index date ( 19 ). In Taiwan, cholestyramine is not available, and, according to NHI's regulations, ezetimibe and niacin could only be prescribed with statin for patients who are difficult to achieve treatment target under statin alone.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients without previous diagnosis of any kind of hyperlipidemia, with incomplete demographics, who were younger than 20 years, or who had undergone renal transplantation prior to the index date were excluded. The remaining patients were divided into four groups (fibrate, statin, combination, and non-user groups) according to their use of lipid-lowering medications within 3 months prior to the index date ( 19 ). In Taiwan, cholestyramine is not available, and, according to NHI's regulations, ezetimibe and niacin could only be prescribed with statin for patients who are difficult to achieve treatment target under statin alone.…”
Section: Methodsmentioning
confidence: 99%
“…Because of such concerns, the use of fibrates for the treatment of dyslipidemia in CKD population remains limited. Studies have evaluated the effectiveness of fibrates in reducing CV risk in populations with mild to moderate ( 14 , 17 , 18 ) and advanced ( 19 ) CKD. However, few studies have evaluated the effectiveness of fibrates in reducing CV risk in patients with ESRD.…”
Section: Introductionmentioning
confidence: 99%
“…Significant improvement in renal oxidative stress, renal function and proteinuria has been recorded with fenofibrate in mice, but no clinical studies have yet investigated the effects of PPAR‐alpha agonists on renal lipid deposition 126 . However, there is evidence supporting kidney protection by fenofibrate from large observational studies and post hoc analysis of randomized clinical trials 127,128 . In the national cohort of Taiwan's National Health Insurance Research Database, the fenofibrate group exhibited the lowest incidence of permanent dialysis (fenofibrate vs nonuser: subdistribution HR [SHR]: 0.78; 95% CI, 0.77–0.80; statins vs fenofibrate: SHR: 1.27; 95% CI, 1.26–1.29; statin‐fenofibrate combination vs fenofibrate: SHR: 1.15; 95% CI, 1.13–1.17) 128 .…”
Section: Therapeutic Implicationsmentioning
confidence: 99%
“…However, there is evidence supporting kidney protection by fenofibrate from large observational studies and post hoc analysis of randomized clinical trials 127,128 . In the national cohort of Taiwan's National Health Insurance Research Database, the fenofibrate group exhibited the lowest incidence of permanent dialysis (fenofibrate vs nonuser: subdistribution HR [SHR]: 0.78; 95% CI, 0.77–0.80; statins vs fenofibrate: SHR: 1.27; 95% CI, 1.26–1.29; statin‐fenofibrate combination vs fenofibrate: SHR: 1.15; 95% CI, 1.13–1.17) 128 . A post hoc analysis of 2636 participants in the fenofibrate arm and 2632 in the placebo arm in the ACCORD Lipid Trial disclosed that during a median follow‐up of 4 years, treatment with fenofibrate was associated with lower rate of eGFR decline (−0.28 ml/min per 1.73 m 2 per year in the fenofibrate group vs. −1.25 ml/min per 1.73 m 2 per year in the placebo group, p < 0.01) and with lower incidence of microalbuminuria (hazard ratio [HR] 0.56, 95% confidence interval [CI] 0.43–0.72, p < 0.001) and macroalbuminuria (HR 0.72, 95% CI 0.57–0.91, p < 0.001), although there was no difference in incidence of CKD (HR 0.92, 95% CI 0.74–1.15, p = 0.46) and/or kidney failure (HR 0.95, 95% CI 0.68–1.33, p = 0.76) 127 .…”
Section: Therapeutic Implicationsmentioning
confidence: 99%
“…A meta-analysis conducted in 2012 reported a lower risk of cardiovascular events and mortality in fibrate users with mild-to-moderate CKD [58]. In a recently reported cohort study of patients with advanced CKD, a cardiovascular risk reduction was reported in the fenofibrate treatment arm while also protecting against incident renal function worsening [59]. Potential nephroprotective mechanisms involve attenuated oxidative stress, inflammation, and apoptosis [60].…”
Section: Treatment Of Dyslipidemia In Ckdmentioning
confidence: 99%